50 students engage in Workshop Enhanced by Web-Based Language Tools - Ruhil Amal, Azmuddin; Zuraina, Ali (UMPSA, 2023)
PEKAN, 19 October 2023 - In an era where digital literacy and proficiency in online learning resources are essential, “Language Leap: Mastering English with Web Wizards” was conducted to bridge the gap and empower students to make effective use of web-based tools for language learning.